Risk of cultivation and effect of mineral fertilization on winter oilseed rape under the conditions of north-east Bulgaria. - Tonev , Tony K. (Plant Breeding and Seed Science, 2006)
This investigation provides data from two field trials. During the period 1999-2002 a comparative investigation was carried out to test winter oilseed rape varieties Polo, Marita, Bor, Kana, Gara, Mar and Leo in order to select the most productive one to continue the studies on agronomic factors. During the period 2000-2004 a fertilization trial was initiated with variety Gara to investigate the rates and ratios of macro-fertilization (NPK) in winter oilseed rape under the conditions of Dobroudja region. Sixty combinations were studied as follows: 3 rates of fertilization with potassium (0, 40, and 80 kg × ha –1 K2O), 4 rates of phosphorus fertilization (0, 40, and 120 kg × ha-1 P2O5), and 5 rates of nitrogen fertilization (0, 40, 120 and 160 kg × ha –1 N). During the 5-year period, in two of the years oilseed rape was not harvested. Two risk periods were established which limited the area for growing of oilseed rape in Bulgaria: August-September and the winter period. The sowing period was characterized with a risk of drought in 26.9% of the years, or by intensive rainfalls and formation of soil crust, both factors limiting the formation of a regular spatial pattern of the crop. The successful wintering of oilseed rape can not be ensured because in 34.6% of the years for a period of 52 years, days with air temperature –15°C, or insufficient snow cover, were registered. The comparative testing of the oilseed rape varieties revealed that variety Gara showed the highest productivity and stability by years under the conditions of North-East Bulgaria. The other varieties did not differ by this criterion. The investigation on NPK-fertilization established that averaged for the rates of potassium and phosphorus fertilization, phosphorus was the factor with the highest effect on oilseed yield from rape up to rate N160. The tendency towards significant differences according to the previous investigated rate continued up to rate N80 in dry years, and up to N120 in years with good moisture reserve. During the year with good moisture reserve, a well expressed effect from the independent use of phosphorus and potassium fertilization was established, as well as the interaction between nitrogen and phosphorus, and phosphorus and potassium, which implies the necessity of the obligatory presence of phosphorus in the fertilization rate with moderate doses (P80). As a result from this, fertilization with N120P80 can be recommended as agronomically optimal under the conditions of Dobroudja region.